2010
DOI: 10.1021/jp105588n
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Photoelectron Spectra of Conjugated Oligomers with Time-Dependent Density Functional Theory

Abstract: With the aim of producing accurate band structures of conjugated systems by employing the states of cations, TDDFT calculations on conjugated oligomer radical cations of thiophene, furan, and pyrrole with one to eight rings were carried out. Benchmarking of density functional theory and ab initio methods on the thiophene monomer shows that the ∆SCF ionization potential (IP) is most accurate at the B3LYP/6-311G* level. Improvement of the basis set beyond 6-311G* leads to no further changes. The IP is closer to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 49 publications
(85 reference statements)
2
23
0
1
Order By: Relevance
“…An additional issue with DFT is that all properties depend too strongly on system size. Thus, the decrease in IPs with increasing oligomer length is overestimated which means that IPs of long oligomers and polymers are too low, even with functionals that predict IPs of small molecules correctly . This problem can also be addressed with certain range‐separated hybrid functionals …”
Section: Ion States Band Structures and Orbital Energiesmentioning
confidence: 99%
See 3 more Smart Citations
“…An additional issue with DFT is that all properties depend too strongly on system size. Thus, the decrease in IPs with increasing oligomer length is overestimated which means that IPs of long oligomers and polymers are too low, even with functionals that predict IPs of small molecules correctly . This problem can also be addressed with certain range‐separated hybrid functionals …”
Section: Ion States Band Structures and Orbital Energiesmentioning
confidence: 99%
“…As mentioned previously, the first IP can be calculated with the ΔSCF method as the energy difference between energies of neutral molecule and cation. The higher IPs can be obtained with TDDFT by calculating excited states of the cations, selecting the states that correspond to the ions that have the hole in the appropriate orbitals (i.e., the states that transfer β‐electrons from lower‐lying orbitals to the semi‐occupied molecular orbital (SOMO)), and adding the excitation energies to the first IP . Comparison of excited state energies of cations with orbital energies has revealed that DFT with certain range‐separated hybrid functionals produces accurate orbital energies for valence and innervalence electrons down to around −30 eV …”
Section: Ion States Band Structures and Orbital Energiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Although many recent quantum mechanical studies using high level post-HF methods, such as Møller-Plesset perturbation theory (MP2), coupled-cluster singles/doubles (CCSD) and coupled-cluster triples CCSD(T) in combination with a number of large basis sets such as TZV2P+f [17] and using various Density Functional Theory (DFT) models including BHLP, B3LYP, BLYP, BP86, local spin-density approximation (LSDA) [26] and BPW91 [13] models, the puzzle of E-Fc or S-Fc remains. Nevertheless, all consistently suggest that the eclipsed Fc exists in equilibrium as the minimum structure of Fc [2,17,18,20,27]. Studies using the B3LYP/m6-31G(d) model indicated that in addition to the quantum mechanical method, the basis set needs to including more d-functions of Fe [2,3].…”
Section: Introductionmentioning
confidence: 99%